Use of Assessment Indicators to Forecast Market Promotion of Products - V. Clopova , Anna; V. Skripin, Petr; I. Shpak, Tatiana; B. Zhukov, Roman (KnE Life Sciences, 2021)
During recent years the trend to tighten competitiveness has been increasing globally almost in all industries, although before then it was absent in many countries and economic sectors. This article touches upon the main issues regarding the competitiveness of enriched curd products with prebiotic substances. On the basis of a consumer survey, the calculation of advantageous indicators was performed. According to the results of the ranking of quality indicators, the following maximum values were accepted: taste and smell, form and consistency, titratable acidity, amino acid composition, and vitamin and mineral composition. A comparative analysis of consumer qualities of curd products is given. According to the results of the assessment of the quality of curd products, it can be concluded that competitive advantage belongs to a curd product enriched with cedar oil cake, lactulose syrup and whey proteins. This is followed by the curd product enriched with cedar oil cake and lactulose syrup, and then the integral indicator in the curd sample enriched with cedar oil cake. The integral indicators of curd cream and curd cheese have low values: 0.16 and 0.145, respectively. Thus, the developed curd products enriched with prebiotic substances will be in demand in the modern market of curd products. Keywords: competitiveness, complex quality indicator, curd products, cedar oil cake, whey protein, lactulose